Understanding How Outbound Trainers Build Customer Satisfaction: A Multi-Case Qualitative Study of Outbound Trainers and Their Clients in Batu, Indonesia - Prasetyo, Allan Awangga (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study looks at how outdoor trainers use different methods to boost client satisfaction. Since these programs involve constant interaction, keeping customers happy plays a key role in maintaining repeat business while supporting financial sustainability over time. Background Problems: The issue being studied involves inconsistent results in outbound training when it comes to meeting client expectations, made more complex by the abstract nature of the service and how much it depends on the trainer’s skills. This study asks: From both trainers’ and participants’ viewpoints, what actions lead to higher satisfaction in these programs? Novelty: This work fills a missing piece in existing studies through detailed qualitative analysis of how trainers operate offering their viewpoint, which earlier research often ignores despite centering on participants’ results. Research Methods: This multi-case qualitative research gathered information from two skilled outbound trainers and their clients in Batu, Indonesia using semi-structured interviews, observational methods without participation, along with examination of written records. The material was processed through thematic coding techniques. Finding/Results: The results show a clear pattern of four main approaches to boosting satisfaction: first, tailoring plans after detailed analysis of user needs; also, strong support using inclusive methods; next, deeper connections that go past simple exchanges; finally, ongoing adjustments guided by broad feedback. When trainer and participant views align, it becomes evident that success depends not only on skill but equally on genuine personal engagement. Conclusion: The key takeaway here, program effectiveness in outbound training hinges on solid instructional design along with the facilitator’s skill in promoting group connection and engaging learning. This research offers practical guidance: helping providers improve delivery standards while enabling customers to make smarter choices when picking partners.